2014
DOI: 10.1111/modl.12124
|View full text |Cite
|
Sign up to set email alerts
|

How I See What You're Saying: The Role of Gestures in Native and Foreign Language Listening Comprehension

Abstract: In what ways do native language (NL) speakers and foreign language (FL) learners differ in understanding the same messages delivered with or without gestures? To answer this question, seventh‐ and eighth‐grade NL and FL learners of English in the United States and Norway were shown a video of a speaker describing, in English, a cartoon image that the viewers could not see. For half the viewers, the speaker's gestures were visible; for the others they were not. Participants drew a picture of each description, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 50 publications
5
34
2
Order By: Relevance
“…Then, participants were informed that they were going to perform a narrative comprehension task, and were directed to read the instructions carefully. Instructions (adapted from Dahl and Ludvigsen, 2014) were available in both French and English and were as follows:…”
Section: Drawing Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, participants were informed that they were going to perform a narrative comprehension task, and were directed to read the instructions carefully. Instructions (adapted from Dahl and Ludvigsen, 2014) were available in both French and English and were as follows:…”
Section: Drawing Taskmentioning
confidence: 99%
“…Speech is a multimodal act that allows for listeners to make use of both auditory as well as visual cues to make sense of the incoming message. Numerous studies have shown that speech produced with referential gestures 1 boost both comprehension and recall in the L1 (Riseborough, 1981;Cohen and Otterbein, 1992; among many others), with very few studies showing no effects (e.g., Austin and Sweller, 2014;Dahl and Ludvigsen, 2014). Similarly, positive results have also been found in the L2 (Sueyoshi and Hardison, 2005;Tellier, 2008;Kelly et al, 2009;Macedonia et al, 2011; among many others).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Listeners often perceive visual input that not only consists of visible speech, but also iconic hand gestures, which can convey semantic information about the speech signal. Previous work has demonstrated that listeners integrate this semantic information with speech (Kelly, Creigh, & Bartolotti, ) and that both native and non‐native listeners can benefit from semantic information that is conveyed by gestures (Dahl & Ludvigsen, ; Sueyoshi & Hardison, ), especially when speech is degraded (Drijvers & Özyürek, , , ; Drijvers et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the role of videos in L2 listening tests produced mixed results. Non-verbal information in videos was found to improve test scores (Ginther, 2002;Jones and Plass, 2002;Sueyoshi and Hardison, 2005;Wagner, 2010bWagner, , 2013aDahl and Ludvigsen, 2014). However, the score difference was not pronounced (Coniam, 2001;Cubilo and Winke, 2013;Batty, 2015;Suvorov, 2015).…”
Section: Task Settingmentioning
confidence: 80%